Diabetes is a risk factor for knee osteoarthritis progression. Issue 6 (June 2015) - Eymard, F.; Parsons, C.; Edwards, M.H.; Petit-Dop, F.; Reginster, J.-Y.; Bruyère, O.; Richette, P.; Cooper, C.; Chevalier, X.
Summary: Purpose: Recent studies have suggested that metabolic factors (obesity, diabetes, hypertension and dyslipidemia) and their clustering in metabolic syndrome (MetS) might be involved in the pathophysiology of knee osteoarthritis (OA). We investigated their impact on radiographic progression by an annualised measure of the joint space narrowing (JSN) of the medial tibiofemoral compartment. Methods: 559 patients older than 50 years with symptomatic knee OA were recruited for the placebo arm of the SEKOIA trial. The presence of diabetes, hypertension and dyslipidemia was determined at baseline interview. Body mass index (BMI) was calculated, obesity was considered >30 kg/m 2 . MetS was defined by the sum of metabolic factors ≥3. Minimal medial tibiofemoral joint space on plain radiographs was measured by an automated method at baseline and then annually for up to 3 years. Results: The mean age of patients was 62.8 [62.2–63.4] years; 392 were women. A total of 43.8% was obese, 6.6% had type 2 diabetes, 45.1% hypertension, 27.6% dyslipidemia and 13.6% MetS. Mean annualised JSN was greater for patients with type 2 diabetes than without diabetes (0.26 [−0.35 to −0.17] vs 0.14 [−0.16 to −0.12] mm; P = 0.001). This association remained significant after adjustment for sex, age, BMI, hypertension and dyslipidemia ( P = 0.018). In subgroup analysis, type 2 diabetes was a significant predictor of JSN in males but not females. The other metabolic factors and MetS were not associated with annualised JSN. Conclusion: Type 2 diabetes was a predictor of joint space reduction in men with established knee OA. No relationships were found between MetS or other metabolic factors and radiographic progression.